Hybrid houses and dispersed communities: Negotiating governmentality and living well in Peruvian Amazonia. Issue 119 (February 2021) - Killick, Evan
Abstract: Focused on one officially recognised Ashaninka Comunidad Nativa ('Native Community') on the Ucayali River in Peruvian Amazonia, the article examines indigenous responses to the demands and expectations of being part of the Peruvian state and the associated techniques of government. The article traces the origins of such communities to the 1974 Law of Native Communities, showing how their form and function has been produced through the constant interplay between external and internal conceptions of the proper organisation of communal life. Drawing on Lévi-Strauss' notion of bricolage as well as more recent discussions of 'indigenous creolisation, ' hybridity and the 'openness' of Amerindian societies the article emphasises the productivity of focusing on the everyday constructions of hybrid forms rather than distinct categories. In a final section it draws out the implications of this understanding to recent political discussions and uses of the concept of Buen Vivir ('living well'). In this way it argues that while emphasising and projecting particular ideas of indigenous culture may be one strategy for indigenous survival and action, the ability to combine and mix new forms of living remains a key component of contemporary indigenous lives in Amazonia.